Types of Exemption from Testimony under the Legislation of Ukraine and the Legislation of the Countries of the European Union - SEMENIUK, Iryna (University Scientific Notes, 2022)
A comparative analysis of the criminal legislation of Ukraine and the member states of the European Union regarding exemption from punishment is carried out. Types of exemption from punishment are defined. The main areas of improvement of the legislation of Ukraine on criminal liability in the specified area are outlined. Emphasis is placed on the problems that may arise at various stages of the implementation of criminal liability, the imposition of a sentence on a convicted person and its execution. The criminal-legal consequences of establishing these facts are regulated by the criminal laws of both Ukraine, in particular within the framework of the institutions of exemption from punishment and its serving, and the laws of foreign countries. A literary review of national and foreign legal literature is carried out regarding the division of exemption from punishment into types and the basis of various criteria is investigated, including: the degree of proximity of the punishment to the person who committed the criminal offense; degree of mandatory application of exemption; presence of special duties of the convicted person; according to the legal facts with which the legislator connects exemption from punishment and its serving; criterion of conditionality/unconditionality of further behaviour of a person released from punishment. It is indicated that, taking into account the variety of types of exemption from punishment established in the provisions of national criminal laws, it can be stated that the most successful criterion for their classification is the stage of the court proceedings at which they can be applied, namely, depending on the decision regarding the person of the guilty verdict. It is emphasized that the legislation of the EU states provides for various types of exemption from punishment, which can be applied to a person against whom a guilty verdict has not been passed and, accordingly, no punishment has been imposed, and only one of them is provided for in the Criminal Code of Ukraine: this exemption from punishment in connection with the statute of limitations of criminal liability (Part 5 of Art. 74 of the Criminal Code of Ukraine). At the same time, it is advisable to pay attention to different normative and legal assessment of the same circumstances.
Keywords: punishment; exemption from punishment; types of exemption from punishment; legislation of European Union states; domestic legislation